Application of the Kano model for a better understanding of customer requirements in higher education: A pilot study - Peter Madzík; Pavol Budaj; Dalibor Mikuláš; Dominik Zimon (Administrative Sciences, 2019)
Various pieces of information and knowledge turn into "know-how" simply by their application in the market. This applies to all spheres of activities. It is therefore important to know and understand the requirements of customers already in the stage of making a product, and to confront these with the possibilities of a producer. In this article we are exploring the possibilities of a better understanding of the requirements of customers and stakeholders in the process of the creation of products in educational services. In particular, we examined seven general requirements: practice orientation, ethical orientation, research orientation, quality resources, innovation orientation, skills orientation, and quality staff. We use the Kano model on a pilot sample of respondents at an institution of higher education. Our results showed that "practice orientation" and "quality resources" are the most stable requirements, while "quality staff" is the least stable. The most linear requirement (the same effect on satisfaction and dissatisfaction) is "innovation orientation". "Research orientation" belongs to attractive requirements and we also found that in the case of "ethical orientation" there are weak relations between positive and negative responses in our survey. The "skills orientation" proved to be too general, and our research shows that it could be indifferent. It is therefore advisable to specify the investigated skills when investigating requirements on educational services. The main contribution based on the proposed research procedures is an effective linking of customers and producers already from the beginning of constructing a value chain. Investing in sophisticated management approaches when modelling products and processes can thus become a significant source of the competitive advantage of an educational institution. At the same time, it is a contribution to better placing of its graduates in the labor market.
Keywords: 350; quality management; requirements; education; Kano model; questionnaire